Research on the multi-objective optimization of energy consumption and indoor environment: a case study of residential structures in hot-summer and cold-winter regions - Zhang, Mingyan; Song, Jia (Frontiers in Built Environment, 2026)
Balancing the relationship between building energy consumption and the health performance of the indoor environment has emerged as a crucial scientific issue for the sustainable development of residential buildings. Drawing upon existing regulations and standards, this paper employs the building energy use intensity (EUI) as an indicator of energy consumption and systematically selects four key parameters, namely, the thermal - humidity environment, light environment, sound environment, and air quality, as evaluation indices for indoor health and comfort. A comprehensive quantitative evaluation method for the health performance of the indoor environment is developed. Taking a residential building in Nanjing as a case study, a multi - objective optimization model is established based on the energy consumption and health performance of the indoor environment to attain the dual objectives of minimizing the EUI and maximizing the level of health and comfort. The optimization results indicate that the building EUI index is notably reduced by 1.96%–6.41%, and the duration of indoor environmental health and comfort is extended by 13–117 h. Based on these results, optimal solutions highlighting different optimization objectives can be selected for diverse groups of people with varying requirements.